Kierkegaard, Aesthetics, and Selfhood : the Art of Subjectivity. - Jothen, Peder (Ashgate studies in theology, imagination, and the arts., 2016)
In the digital world, Kierkegaard's thought is valuable in thinking about aesthetics as a component of human development, both including but moving beyond the religious context as its primary center of meaning. Seeing human formation as interrelated with aesthetics makes art a vital dimension of human existence. Contributing to the debate about Kierkegaard's conception of the aesthetic, Kierkegaard, Aesthetics, and Selfhood argues that Kierkegaard's primary concern is to provocatively explore how a self becomes Christian, with aesthetics being a vital dimension for such self-formation. At a b.